The opinion of breast cancer patients on the non-pharmacological pain-relief methods - Mamčenkovaitė, Evelina; Lekauskaitė, Aušra (Slauga. Mokslas ir praktika, 2021)
Aim. To determine the opinions of II and III stage breast cancer patients on the non-pharmacological pain-relief methods. Methods. The research was performed from November 2019 to January 2020 in the Oncology and Hematology department of Lithuanian University of Health Sciences Kaunas Clinics. Patients completed a survey of 25 questions. 33 surveys were analysed. Statistical data analysis was performed using IBM SPSS Statistics 25.0 and Microsoft Excel 2016 software packages. Results. Almost half of the survey participants were unaware of the pain-relief methods, had not tried any of physical pain-relief methods and did not know or have an opinion about their effectiveness. Half of the survey participants thought that music, spiritual and cognitive behavioral therapies can relieve the pain. Also, more than half of the participants had not tried any psychological pain-relief methods and did not know or have an opinion about their effectiveness. More than half of the participants did not know if it is possible to reduce pain using medical marijuana, virtual reality glasses and hypnosis.